2019
DOI: 10.1016/j.ahj.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of myocardial infarction symptoms and perceptions of self-risk in Tanzania

Abstract: Background Little is known about community knowledge of myocardial infarction symptoms and perceptions of self-risk in sub-Saharan Africa. Methods A community survey was conducted in northern Tanzania, where the prevalence of cardiovascular risk factors is high. Households were selected randomly in a population-weighted fashion and surveys were administered to self-identified household healthcare decision-makers. Respondents were asked to list all symptoms of a heart at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
4
15
1
Order By: Relevance
“…Patients cited unawareness of the seriousness of their symptoms as the primary reason for the delayed hospital presentation. This is consistent with prior community-based research from northern Tanzania that found very few patients recognized cardiovascular causes of chest pain and shortness of breath, 26 , 27 and underscores the need for community education regarding symptoms of cardiovascular disease and appropriate care seeking for such symptoms. Beyond symptom knowledge, a complex set of factors likely contributes to delayed care seeking in this population, and additional theory-based research is needed to identify other modifiable determinants of pre-hospital delays among patients with acute CVD in Tanzania.…”
Section: Discussionsupporting
confidence: 88%
“…Patients cited unawareness of the seriousness of their symptoms as the primary reason for the delayed hospital presentation. This is consistent with prior community-based research from northern Tanzania that found very few patients recognized cardiovascular causes of chest pain and shortness of breath, 26 , 27 and underscores the need for community education regarding symptoms of cardiovascular disease and appropriate care seeking for such symptoms. Beyond symptom knowledge, a complex set of factors likely contributes to delayed care seeking in this population, and additional theory-based research is needed to identify other modifiable determinants of pre-hospital delays among patients with acute CVD in Tanzania.…”
Section: Discussionsupporting
confidence: 88%
“…The reasons for the pronounced delay in care-seeking observed in our study are likely myriad, but lack of patient awareness may be contributing to the problem. A recent study found that most Tanzanians did not associate chest pain with cardiovascular diseases like ACS [15,16], suggesting that lack of patient appreciation for the potential seriousness of these symptoms may explain their delayed care-seeking. Further research is needed to understand and intervene upon other barriers to prompt hospital presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Some have postulated that ACS may be under-diagnosed in SSA due to poor community awareness and delayed healthcare seeking, inadequate physician training, and lack of diagnostic and treatment capacity [34]. Indeed, recent community surveys in Tanzania found that few adults knew the symptoms of ACS or would present to a hospital for such symptoms, whereas the large majority of adult Tanzanians would present to a hospital for stroke-like symptoms [35., 36., 37.]. These results suggest that patient knowledge and behaviors may be driving ACS under-detection in hospital-based studies in SSA.…”
Section: Discussionmentioning
confidence: 99%